High‐Power Lithium Metal Batteries Enabled by High‐Concentration Acetonitrile‐Based Electrolytes with Vinylene Carbonate Additive - Peng, Zhe; Cao, Xia; Gao, Peiyuan; Jia, Haiping; Ren, Xiaodi; Roy, Swadipta; Li, Zhendong; Zhu, Yun; Xie, Weiping; Liu, Dianying; Li, Qiuyan; Wang, Deyu; et al. (Advanced functional materials, 2020)
To enable next‐generation high‐power, high‐energy‐density lithium (Li) metal batteries (LMBs), an electrolyte possessing both high Li Coulombic efficiency (CE) at a high rate and good anodic stability on cathodes is critical. Acetonitrile (AN) is a well‐known organic solvent for high anodic stability and high ionic conductivity, yet its application in LMBs is limited due to its poor compatibility with Li metal anodes even at high salt concentration conditions. Here, a highly concentrated AN‐based electrolyte is developed with a vinylene carbonate (VC) additive to suppress Li+ depletion at high current densities. Addition of VC to the AN‐based electrolyte leads to the formation of a polycarbonate‐based solid electrolyte interphase, which minimizes Li corrosion and leads to a very high Li CE of up to 99.2% at a current density of 0.2 mA cm‐2. Using such an electrolyte, fast charging of Li||NMC333 cells is realized at a high current density of 3.6 mA cm‐2, and stable cycling of Li||NMC622 cells with a high cathode loading of 4 mAh cm‐2 is also demonstrated. A highly concentrated acetonitrile‐based electrolyte with a vinylene carbonate additive is developed to significantly suppress Li+ depletion and side reactions on Li metal anode (LMA) at high current densities. High‐power Li metal batteries can be obtained using this electrolyte with a much stabilized LMA and accelerated ion transfer.